Prototype Design of Parallette Equipment for Callisthenic Sports with PLA (Polylactic Acid) Filament Material Using 3D Printer - Indro Prakoso; Ayu Anggraeni Sibarani; Whimpi Hasta Robbi (School of Industrial and System Engineering, Telkom University, 2022)
Nowadays, sport is not only a necessity but also a lifestyle. Sport is not only done outdoors but can also bedone independently indoors. One exercise that is easy to do independently is calisthenics. In general,calisthenics can be done with a tool called a parallette. Parallette equipment manufacturers currently stilluse wood materials and conventional production processes and do not have product variations. A potentialproduction process that can be adapted to make parallette equipment is additive manufacturing 3D printerswith PLA (Polylactic Acid) filament material. The process is carried out through several stages: 3D design,printing using a 3D printer, assembly, and finishing. The production process of a parallette tool with a 3Dprinter takes a standard time of 3123.02 minutes. The longest time occurs when printing with a 3D printerfor grip parts (2 parts) and parallette legs (4 parts). The gross production cost for a set of paralletteequipment is Rp. 101,327. Production of calisthenic equipment with PLA (Polylactic Acid) filamentmaterial using a 3D printer can be used as an alternative to replace wood-based parallette products withconventional manufacturing processes. Sports equipment manufacturers can also use this product as achoice and variety offered to customers.